Laparoscopic Management of a Torsioned Round Ligament Fibroid - Kaya, Cihan (Oman Med J, 2018)
Round ligament fibroids are rare tumors and can present as inguinal, adnexal, or vulvar masses. Preoperative diagnosis can be made by ultrasonography or magnetic resonance imaging (MRI). A 28-year-old virgin female presented with pelvic pain that persisted for a few days. Her sonographic evaluation detected a well-defined hyperechoic 45 × 40 mm right adnexal mass interfering endometrioma. A contrast-enhanced pelvic MRI showed a 43 × 39 × 32 mm solid mass located in the right adnexa. Laparoscopic exploration revealed a well-defined double torsion around the peduncle pinky solid mass arising from the right round ligament. The mass was resected with the final histopathological diagnosis being leiomyoma. The diagnosis of round ligament fibroids can be challenging, and laparoscopy is one of the first options where surgical facilities are available.